Bad Guys - Perifel, Pierre; Cohen, Etan; Ross, Damon (Producer); Huntley, Rebecca (Producer); Rockwell, Sam; Maron, Marc; Awkwafina, 1988-; Robinson, Craig, 1971-; Ramos, Anthony; Ayoade, Richard, 1977-; Beetz, Zazie; Borstein, Alex; et al. (Universal City, CA Universal Studios, 2022)
The criminal crew of Mr. Wolf, Mr. Snake, Mr. Piranha, Mr. Shark and Ms. Tarantula are about to attempt their most challenging con yet: becoming model citizens.
Originally released as a motion picture in 2022.
Based on the books by Aaron Blabey.
Aspect ratio 2.39:1.
"Technicolor."
Bonus: Maraschino Ruby exclusive short; deleted scenes; Devise the plan: making The bad guys; Assemble the crew; It's showtime: cast table read; Snake's frozen pop shop; From the drawing room; feature commentary with director Pierre Perifel, producer Damon Ross, head of story Nelson Yokota, head of character animation JP Sans and production designer Luc Desmarchelier.
Music by Daniel Pemberton ; film editor, John Venzon ; production designer, Luc Desmarchelier.
Keywords: Predatory animals -- Juvenile films; Animals -- Juvenile films; Criminals -- Juvenile films; Good and evil -- Juvenile films; Robbery -- Juvenile films; Blu-ray video discs; Action and adventure films; Animated films; Caper films; Children's films; Comedy films; Computer animation films; Feature films; Fiction films; Film adaptations; Juvenile works; Video recordings for people with visual disabilities; Video recordings for the hearing impaired